Resounding the sublime : music in English and German literature and aesthetic theory, 1670-1850 - Stanyon, Miranda, 1984- (Sound in history., 2021)
"What does the sublime sound like? Harmonious, discordant, noisy, rustling, silent? Miranda Eva Stanyon rereads and resounds this crucial aesthetic category in English and German literatures of the long eighteenth century from a musical perspective and shows how sonorous sublimes lay at the heart of a central and transformative discourse. For Enlightenment and Romantic era listeners, the musical sublime represented a sonic encounter of the most extreme kind, one that tested what humans were capable of feeling, imagining, thinking, and therefore becoming. The sublime and music have not always sung from the same hymn sheet, Stanyon observes. She charts an antagonistic intimacy between the two, from the sublime's rise to prominence in the later seventeenth century, through the upheavals associated with Kant in the late eighteenth century, and their reverberations in the nineteenth. Offering readings of canonical texts by Longinus, Dryden, Burke, Klopstock, Herder, Coleridge, De Quincey, and others alongside lesser-known figures, she shows how the literary sublime was inextricable from musical culture, from folksongs and ballads to psalmody, polychoral sacred music, and opera. Deeply interdisciplinary, Resounding the Sublime draws literature into dialogue with sound studies, musicology, and intellectual and cultural history to offer new perspectives on the sublime as a phenomenon which crossed media, disciplines, and cultures."--